Comparison of the Effectiveness of Reality Therapy and Acceptance and Commitment Therapy on Academic Procrastination in Female Students with Symptoms of Nomophobia - Ghoreishi , Mansoureh Sadat; Khakpour, Reza; Rezakhani, Simindokht (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Reality Therapy on academic procrastination in female high school students with symptoms of nomophobia. This research is classified as fundamental research and employs a quasi-experimental design with a pre-test, post-test, and follow-up, along with a control group. The statistical population consisted of all female high school students in the second cycle of secondary education in District 3 of Tehran during the 2023–2024 academic year. The sampling method was convenience sampling, and a total of 45 participants were selected. Data were collected using the Nomophobia Questionnaire by Yildirim and Correia (2015) and the Academic Procrastination Questionnaire by Solomon and Rothblum (1984). The protocol for the group therapy sessions based on ACT (Hayes et al., 1999) was adapted from Khatibi et al. (2020) and implemented over eight sessions, while the intervention protocol based on Reality Therapy was adapted from Eskandari (2017) and also conducted over eight sessions. Data analysis was performed using repeated measures analysis of variance. The results indicated a significant difference in the effectiveness of ACT and Reality Therapy on academic procrastination in female high school students with symptoms of nomophobia, with Reality Therapy leading to a greater reduction in academic procrastination compared to ACT.